2019
DOI: 10.1186/s40644-019-0264-y
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted imaging for identifying patients at high risk of tumor recurrence following liver transplantation

Abstract: BackgroundTumor recurrence is the major risk factor affecting post-transplant survival. In this retrospective study, we evaluate the prognostic values of magnetic resonance (MR) diffusion-weighted imaging (DWI) in liver transplantation for hepatocellular carcinoma (HCC).MethodsFrom April 2014 to September 2016, 106 HCC patients receiving living donor liver transplantation (LDLT) were enrolled. Nine patients were excluded due to postoperative death within 3 months and incomplete imaging data. The association be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Similar controversial results regarding ADC mean in the prediction of HCC with MVI were reported by two studies stating that ADC mean is significantly lower in HCCs with MVI than in HCCs without MVI [37,38]. However, another three studies reported no significant differences between HCCs with MVI and HCCs without MVI [39][40][41]. To date, no standardized ADC measuring method has been available for liver DWI study.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Similar controversial results regarding ADC mean in the prediction of HCC with MVI were reported by two studies stating that ADC mean is significantly lower in HCCs with MVI than in HCCs without MVI [37,38]. However, another three studies reported no significant differences between HCCs with MVI and HCCs without MVI [39][40][41]. To date, no standardized ADC measuring method has been available for liver DWI study.…”
Section: Discussionsupporting
confidence: 53%
“…To date, no standardized ADC measuring method has been available for liver DWI study. Some researchers tend to draw an ROI avoiding the cystic necrotic part, and the hemorrhage of the measured lesion [28,29,35,38,40,42,43], while some draw the ROI on the entire liver tumor [27,34,36,37,39,41]. This may explain the diversity of ADC mean measurements and the correlation between MVI and the histo-pathologic grade of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…This situation might be the reason for the missing correlation. Nevertheless, despite some studies reporting a correlation between lower ADC values with early recurrence after liver transplantation [10] or SIRT [29], and lower OS after TACE or SIRT [30], all of these studies are retrospective single-centre studies; and other studies have reported no such correlation [15]. HCC has mostly a heterogeneous intratumoral architecture, especially in large lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with the same BCLC class or Child-Pugh grade do not benefit from the treatments equally, and there is a need for additional features to cover all the variations in clinical outcomes within the same category. Multiple studies have investigated a correlation between radiological appearances and recurrence, survival or histopathological grade of the lesions [10,11], but most of these studies investigated patients who underwent resection or transplantation. Evaluation of such imaging features after SIRT or sorafenib treatment is lacking in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion weighted imaging is another promising MRI feature to predict HCC treatment outcome. A single center trial reported lower apparent diffusion coefficient values, which predicted early recurrence after LT ( 51 ). However, the heterogenous nature of HCC, especially in larger lesions, could potentially limit the value of the diffusion technique in more advanced patients outside MC.…”
Section: Beyond Afp–pet Hepatobiliary Mri and Other Biomarkersmentioning
confidence: 99%